Lange Q & A pharmacy - Hall, Gary D.; Reiss, Barry S. (New York : McGraw-Hill Medical., 2011)
"1500 questions and answers deliver unmatched preparation for the NAPLEX NEW COMPANION CD-ROM includes 12 patient profiles and a more! LANGE Q&A Pharmacy, 10e is the most effective and comprehensive review available for the NAPLEX. The book features 1500 questions and answers with detailed answer explanations along with tried-and-proven tips for boosting exam performance.The questions cover all major testing areas, including pharmacy, pharmacology, pharmaceutical calculations and compounding, biopharmaceutics and pharmacokinetics, and health equipment and supplies. Features companion CD includes 12 patient profiles; a listing of more than 200 drugs by generic name that the author considers the most likely to be dispensed by pharmacists; and a cross-reference of trade and generic drug names. Herbal and dietary supplements are included. Helps you recognize all frequently dispensed drugs, including top sellers and newly licensed ones."--
Keywords: Pharmacy; Pharmacological Phenomena; Technology, Pharmaceutical